National Strategy for Growth and Reduction of Poverty ll - MKUKUTA Secretariat, Ministry of Finance and Economic Affairs (Dar es Salaam Ministry of Finance and Economic Affairs, 2010)
This is the Second National Strategy for Growth and Reduction of Poverty (NSGRP) to be implemented starting from 2010/11 to 214/15. In Kiswahili, it is known as Mpango wa pili wa Kukuza Uchumi na Kuondoa Umaskini Tanzania or NSGRP II. As with MKUKUTA I (2005/6-2009/10) the focus continues to be that of accelerating economic growth, reducing poverty, improving the standard of living and social welfare of the people of Tanzania as well as good governance and accountability. MKUKUTA ll, like its predecessor, is a vehicle for realizing Tanzania's Development Vision 2025, the Millennium Development Goals (MDGS) and the aspirations of the ruling party's Election Manifesto (201-2015)
Keywords: Income Poverty, Good Governance Accountability Social Well Being